PRESCRIBING PATTERN OF PSYCHOTROPIC AGENTS IN RURAL TERTIARY CARE TEACHING HOSPITAL - Venkataraman, Rajesh; Rayamajhi, Madan; Islam, Shahinur; N, Nanjunda (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: The objectives of the study were to study the prescribing pattern on psychotropic agents at psychiatric department at rural tertiary care teaching hospital, B.G. Nagara. Methods: A prospective and observational study was conducted among psychiatric department (either sex) after considering inclusion and exclusion criteria for the period of 6 months and a total of 300 prescriptions were analyzed. Results: A total of 300 psychiatric patients were enrolled, male 170 (56.67%) patients predominated over females 130 (43.33%) patients. Majority of participants were under age group of 31â€“40 years (28.6%), illiterate (75%), unemployed (52%), and married (84%). Prevalence of mood disorder 109 (36.33%) was high followed by substance used and addictive disorder 53 (17.67%), schizophrenia 46 (15.33%), and psychosomatic medicine 22 (7.33%). Antidepressant (28.59%) was the commonly prescribed group followed by benzodiazepines (14.81%), anticholinergic (7.18%), and anticonvulsants (7.18%). Tricyclic antidepressants drugs amitriptyline (53.44%) was most frequently prescribed an antidepressant. An average number of drugs per prescription was 2.32 out of which 16.91% of drugs were prescribed by their generic name. Conclusion: Selective serotonin reuptake inhibitors (SSRIs) were the most common group, and escitalopram was the most common medication used among the SSRIs. Majority of the drugs were prescribed from essential drug list. This study advocated an overall rational utilization of psychotropic drugs with fewer deviations due to the socioeconomic status of patients and prescription practices of healthcare providers and need to improve prescribing habits to ensure rational use.